NOTAS SOBRE ABEJAS DE LA REGION MAGALLANICA, CHILE (HYMENOPTERA: APOIDEA) - Pérez D’A., Vicente; Petersen C., José (Acta Entomológica Chilena, 2022)
Some new records of bees, geographical distribuiion, and variation of sume characiers are presented here.